Comparative Analysis of Neurogenesis and Cerebral Angiogenesis in the Hippocampal Neurogenic Niche in Animals with Two Experimental Models of Alzheimer’s Disease - Anton S. Averchuk; Maria V. Kukla; Natalia A. Rozanova; Alla V. Stavrovskaya; Alla B. Salmina (Анналы клинической и экспериментальной неврологии)
Introduction. Various animal models are employed to uncover the mechanisms of Alzheimer’s disease (AD) pathogenesis. Understanding brain damage pathogenesis in animal models of neurodegenerative diseases and identifying common patterns inherent to all relevant models is essential for adequate interpretation of findings, development of new models, as well as prevention and therapy strategies.